Regional suitability for agricultural intensification: a spatial analysis of the Southern Agricultural Growth Corridor of Tanzania. Issue 2 (2nd April 2016) - Nijbroek, Ravic P.; Andelman, Sandy J.
Abstract : Global food production will need to increase by 70–110% to meet the growing demand by 2050. Production per capita remains at 1960 levels in Africa while the agriculture sector accounts for 65% of full-time employment and 61% of rural households in Sub-Saharan Africa depend on agriculture for their livelihoods. Globally there is new focus on increasing agricultural investments in Africa. There is a need, however, for understanding regional factors that influence the outcome of agricultural intensification beyond the landscape scale and below the global scale. This paper provides a framework for considering socioeconomic and environmental factors in evaluating suitability for agricultural intensification at the regional scale. The method employs a spatially explicit multi-criteria evaluation based on freely available data that can be applied in any geography. The focus is on the Southern Agricultural Growth Corridor of Tanzania which has an area greater than 28 million hectares. These results indicate that the area considered most suitable for agricultural investment is different when considering multiple criteria compared to considering only potential yield. This approach is important for government planners, funding partners, and development agencies who seek sustainable agricultural intensification in Africa and elsewhere.